VEGETATION AND TEMPERATURE AS DETERMINANTS IN THE EGG-LAYING BEHAVIOR OF HAWKSBILL TURTLES (ERETMOCHELYS IMBRICATA) AND LOGGERHEAD TURTLES (CARETTA CARETTA) - Dian Puspaningrum; Bachtiar Bachtiar; Ernikawati Ernikawati (Journal of Selvicoltura Asean, 2025)
Vegetation and temperature are biophysical parameters that affect sea turtle nesting behavior. Coastal vegetation is essential to the nesting behavior of Loggerhead sea turtles. In contrast to Hawksbill sea turtles, Loggerhead sea turtles preferentially select sandy beaches for nesting. The study aimed to measure the impact of vegetation and temperature on sea turtle nesting behaviors and to offer detailed insights on adaptation and enhanced conservation techniques to save sea turtles from environmental changes. The study was performed on Popaya Island, within the Nature Reserve of Mas Popaya Raja Island, North Gorontalo, from January to March 2023. Identification of population and sample using the purposive sampling method for all turtles observed throughout the observation phase. The findings indicated that Hawksbill turtles (Eretmochelys imbricata) favored nesting in locations characterized by greater plant diversity and density, averaging 195 eggs per nest. Loggerhead turtles (Caretta caretta) deposited a comparatively lower number of eggs (88 eggs) than at other locations (96 - 108 eggs). Some eggs were found in places with no surrounding vegetation. The nesting activity of loggerheads in non-vegetated regions may have been affected by the shallowness of the holes and their comparatively broader width. The sand surface temperature in areas with dense flora and biodiversity decreases, impacting egg-laying activity as one moves further from the vegetation's border.